Environmental impacts of Petroleum Activities on Block 07/03 offshore, Southeast Vietnam - Liem, Tran Thanh; Khoi, Phan Viet; Vinh, Bui Trong (Vietnam Journal of Earth Sciences, 2012)
The aim of this study is to assess the environmental impacts for petroleum activities on block 07/03 offshore, southeast Vietnam. The results of the Environmental Sample Analysis at Block 07/03, from 4 sampling stations for well are distributed in two perpendicular axes at the vicinities of CRD - 2X well are focused to survey. Distance from sampling stations to the well is 1000m. Survey work was conducted aboard the M / V Genesis and the sample were analyzed at the laboratory of the Center’s Safety and Environment in Oil and Gas (CPSE). The results showed that the environmental quality in the study area were in good condition. Level of environmental impacts of drilling operations to this area is relatively low due to drilling operations using low toxicity chemicals and less harmful to the environment. However, the extent of harm caused to the environment will increase due to reservoir testing as well as oil and gas exploitation. Therefore, the combustion process reservoir testing and commercial exploitation in this area should be re-evaluated.